1995
DOI: 10.1557/jmr.1995.0139
|View full text |Cite
|
Sign up to set email alerts
|

The structure and property characteristics of amorphous/nanocrystalline silicon produced by ball milling

Abstract: The structural transformation of polycrystalline Si induced by high energy ball milling has been studied. The structure and property characteristics of the milled powder have been investigated by x-ray diffraction, scanning electron microscopy, high-resolution electron microscopy, differential scanning calorimetry, Raman scattering, and infrared absorption spectroscopy. Two phase amorphous and nanocrystalline Si has been produced by ball milling of polycrystalline elemental Si. The nanocrystalline components c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
134
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(154 citation statements)
references
References 40 publications
19
134
0
1
Order By: Relevance
“…Line broadening is clearly the biggest difference between bulk silicon and as milled sample ( Figure 3A and 3B respectively). This is in agreement with the thorough investigation of Shen et al [27], on the high energy ball-milling of Si, where nanocrystalline grains of Si ranging from 3 to 20 nr were obtained, based on high resolution TEM and XRD line broadening analysis. [27] A combination of pressure induced amorphization and crystalliterefinement-induced arnorphization was proposed to be responsible for this thermodynamically unfavorable process.…”
Section: A --H-----------+------4--supporting
confidence: 92%
See 4 more Smart Citations
“…Line broadening is clearly the biggest difference between bulk silicon and as milled sample ( Figure 3A and 3B respectively). This is in agreement with the thorough investigation of Shen et al [27], on the high energy ball-milling of Si, where nanocrystalline grains of Si ranging from 3 to 20 nr were obtained, based on high resolution TEM and XRD line broadening analysis. [27] A combination of pressure induced amorphization and crystalliterefinement-induced arnorphization was proposed to be responsible for this thermodynamically unfavorable process.…”
Section: A --H-----------+------4--supporting
confidence: 92%
“…The broad a-Si Raman line, peaking at 475 cm-1 indicates considerable amorphization as a result of high-energy milling as reported by Shen et al [27] and concurred by the significant line broadening shown in Figure 3. Contrary to the expected, the 518 cm-1 c-Si Raman peak indicates a pressure induced crystallite-refinement, also witnessed by Shen et al [27] This was explained on the basis of elevated temperatures reached during high energy milling causing a small fraction of the crystals to grow to more perfect crystallites which are responsible for the up-shift of c-Si Raman peak to higher frequencies.…”
Section: Raman Characterization Of Si/siox Nanocompositessupporting
confidence: 87%
See 3 more Smart Citations